Pengaruh Beban Kerja dan Stres Kerja Terhadap Turnover Intention pada Karyawan Holly Mart Kota Bima - Riska Kistin Meirawati; Muhammad Yusuf; Jaenab (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of workload and job stress on turnover intention among Holly Mart employees in Bima City. High workload and job stress have the potential to increase employees' desire to leave the company, so an empirical study is needed to understand the influence of these two factors on turnover intention. This study used a quantitative approach with an associative design. The study population consisted of all 36 Holly Mart employees in Bima City. The sampling technique used saturated sampling, so that the entire population became the study respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that workload had a significant effect on turnover intention, indicating that increasing workload tends to increase employees' desire to leave the company. Job stress also had a significant effect on turnover intention, indicating that high work pressure can encourage employees to seek a more conducive work environment. Simultaneously, workload and job stress had a significant effect on turnover intention with a contribution of 84.0%. These findings indicate that workload management and work stress control are important factors in efforts to reduce turnover intention and increase employee retention at Holly Mart in Bima City.